Geoecological issues of horticulture development in the foothills of the Namangan region of the Republic of Uzbekistan - Koriev Mirzohid Rustamjonovich (Universitas Muhammadiyah Sidoarjo, 2019)
This article describes the possibilities of achieving economic efficiency and environmental stability through the development of horticulture in the foothills of the Namangan region. Also discussed are the features of the spread of the formed geoecological problems caused by irrigation farming and the methods of their prevention.